Towards human cities; how can architects design for wellbeing in a growing urban environment - Gjøs, Eli-Anne (My University, 2024)
The built environment is proven to impact human wellbeing and it is therefore crucial to understand how humans are affected by what is built. Research shows that our built environment triggers emotional responses in us, that can in the long term have negative impacts on our mental health. This issue has already been highlighted in the past by architects, scholars and urbanists, especially in relation to the effects of modernist architecture. However, concrete architectural strategies to enhance the wellbeing and counteract negative impacts of the built environment are still lacking. This thesis investigates how humans are affected by the built environment with a focus on the emotional responses triggered by specific spatial qualities, and proposes architectural strategies to enhance positive responses and counteract the negative. The main purpose of the thesis is to create an understanding of how architects can improve the wellbeing of the growing urban population by designing urban environments with the human cognition such as the visual sensory system in mind, in order to create positive emotional responses in the population in the long term. This is especially important because existing urban environments will densify and expand with 68% of the human population living in cities in 2050. Therefore, this thesis investigates: How can architects promote human wellbeing in a densifying and growing urban environment by designing urban architecture that triggers positive emotional responses in humans? Through the analysis of human-centered architectural theories, practice perspectives, research and theories from the field of cognitive architecture, architectural principles will be extracted and synthesized to form architectural strategies in multiple scales that contribute to the purpose outlined above. Further, the relevance, significance and applicability of these principles will be tested through a design case study in a specific urban context in central Gothenburg. The principles will be used to enhance specific spatial and visual configurations identified in the context in multiple scales. Lastly, reflections will be made on their use within the design process and their success in improving the design outcome in relation to the expected emotional responses.
Keywords: Human-centered architecture, cognitive architecture, emotional response, urban environment, wellbeing